2000
DOI: 10.1115/1.1343086
|View full text |Cite
|
Sign up to set email alerts
|

Rough Wall Modification of Two-Layer k−ε

Abstract: A formulation is developed to apply the two-layer k−ε model to rough surfaces. The approach involves modifying the lν formula and the boundary condition on k. A hydrodynamic roughness length is introduced and related to the geometrical roughness through a calibration procedure. An experiment has been conducted to test the model. It provides data on flow over a ramp with and without surface roughness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 9 publications
4
44
0
Order By: Relevance
“…Turbulence models have therefore received considerable attention in a great number of publications, e.g. [9,10,20,26,53,57,66,67,72].…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…Turbulence models have therefore received considerable attention in a great number of publications, e.g. [9,10,20,26,53,57,66,67,72].…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…Based on the sand grain roughness, Durbin et al (2001) proposed a rough wall modification for the two layer k − ǫ model. An effective displacement of the wall distance origin was introduced and related to the sand grain roughness height through a calibration procedure.…”
Section: Approaches To Calculate a Fully Turbulent Boundary Layer On mentioning
confidence: 99%
“…For two-layer k − models, Durbin et al (2001) suggested a quadratic interpolation for the transitional regime between a plane interface where the turbulent kinetic energy is zero (k = 0), and to the fully rough interface. The corresponding boundary condition for the turbulent kinetic energy above and below the interface took the form…”
Section: Application In Turbulence Modelsmentioning
confidence: 99%
“…Many two-phase turbulence models for pipe and channel flow rely on interfacial friction models to predict the turbulent (axial) momentum flux transported over the interface from one fluid to the other. In Reynolds averaged models, such as k − models, one adopts an interfacial friction model that is often modelled in terms of a roughness scale (e.g., Durbin et al, 2001;Berthelsen and Ytrehus, 2005;Biberg, 2007;de Sampaio et al, 2008), and it is of importance to develop reasonable roughness scale models that can respond to the length, time and energy scales of the turbulence near the interface. Perhaps the most obvious natural system where the roughness scale is central, is the coupling between the ocean surface and the overlying wind (e.g., Charnock, 1955;Wu, 1980;Fernando, 1991).…”
mentioning
confidence: 99%